Potensi Pengenalan Kuliner UMKM Sate Jaso Mandeh Khas Padang Sumatera Barat - Fadelia Wahyu Restuni; Fani Apriliani; Indah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economies, especially in employment absorption and creating new business opportunities. This study explores the potential of introducing Sate Jaso Mandeh, a traditional Minangkabau culinary specialty from Padang, West Sumatra, through MSMEs located in the busy Simpang Haru area. Despite its unique taste and cultural value, Sate Jaso Mandeh remains underrecognized due to limited promotion and visual branding. This research involves designing logos and promotional banners to enhance product visibility and consumer appeal. Findings indicate that effective visual communication can significantly increase customer attraction and sales volume. Challenges such as limited capital, seasonal fluctuations, and operational constraints exist but can be mitigated through digital marketing, training, and collaboration. Strengthening branding and marketing strategies is essential for sustaining and expanding the MSME’s market reach, preserving cultural heritage, and boosting local economic growth.